Potassium feldspar crystal glaze powder for denture, preparation method of glaze powder and denture

By adjusting the composition and preparation method of potassium feldspar crystal glaze powder, combined with the addition of Sc2O3, the problem of insufficient bonding strength of tetragonal phase zirconia ceramics is solved, significantly improving the mechanical and optical properties of the glaze surface and improving the teeth Bondability.

CN117486494BInactive Publication Date: 2024-12-20KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311435763.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-01
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing tetragonal phase zirconia ceramics have insufficient bonding strength and high brittleness, which can easily lead to the problem of falling off or cracking of the restoration.

Method used

Potassium feldspar crystal glaze powder is used to adjust the number, size, morphology and distribution of crystals in the crystal, combined with the addition of Sc2O3, the process performance of the glaze is improved, the microhardness, mechanical strength and refractive index of the glaze surface are improved, and the microhardness, mechanical strength and refractive index of the glaze surface are improved. A glaze powder with a particle size of 3-5 μm is obtained by specific preparation methods such as melting, disc grinding, ball milling and spray drying, forming a high-quality glaze surface.

Benefits of technology

The bonding between the glaze surface and the denture restoration is significantly improved, the mechanical strength and optical properties of the glaze surface are enhanced, making it close to the thermal expansion coefficient of the zirconia ceramic body, and improving the adhesive properties with the teeth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117486494B_ABST
    Figure CN117486494B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of glaze for dentures, and specifically provides a potassium feldspar crystal glaze powder for dentures, a preparation method of the glaze powder and a denture, wherein the glaze powder comprises the following components: 60-67% SiO 2 11‑12.5% ​​Al 2 O 3 1.4-1.7% B 2 O 3 , 0.7-0.85% CaO, 1.25-1.45% ZnO, 2.5-2.9% Li 2 O, 2.5-2.9% Na 2 O, 7-8% K 2 O, 0.4-0.5% ZrO 2 、1-1.2% MgO、0.15-0.25% Y 2 O 3 , 1.4-1.6% BaO and 2-8% Sc 2 O 3 Sc is added to the crystalline glaze 2 O 3 It can affect the crystallization of the crystal phase in the glaze and improve the process performance of the glaze. After firing, the microhardness, mechanical strength and refractive index of the glaze surface are significantly improved, and the combination with the denture restoration is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glazes for dentures, and specifically provides a potassium feldspar crystal glaze powder for dentures, a preparation method of the glaze powder and a denture. Background Art

[0002] Tetragonal zirconia ceramics with the addition of stabilizers such as scandium oxide, yttrium oxide, magnesium oxide or cerium oxide have good mechanical properties, biocompatibility and aesthetics, and are widely used in the field of dental restorations. However, its main disadvantage is the insufficient bonding strength with teeth. This is mainly because zirconium oxide is an inert material with a very low content of surface silicate and glass phase. It has poor adhesion to teeth and is very brittle, which may cause the restoration to fall off or crack. Therefore, surface treatment of tetragonal zirconia ceramics that are stable at room temperature to improve the bonding performance between the restoration and the adhesive has become one of the difficulties in research in recent years. The use of glazing technology does not require special equipment and materials, and the processing time is short. It has a very broad application prospect in solving this problem.

[0003] The surface of zirconia ceramics after glazing is a feldspar ceramic material, which mainly exists in a mixture of feldspar crystal phase and glass phase. The production process of potassium feldspar crystal glaze is simple, does not require complex equipment and too high cost, and the color is closest to teeth, which can meet the aesthetic requirements of consumers. However, it also has the problems of low strength, poor toughness, and inability to withstand large loads, which limits its application. This problem can be solved by changing the number, size, morphology and distribution of crystals in the crystal glaze. The method of controlling crystallization can improve the strength of the glaze on the one hand, and on the other hand, it can also adjust the thermal expansion coefficient of the glass to make it close to that of the zirconia ceramic body. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a potassium feldspar crystal glaze powder for dentures, a preparation method of the glaze powder and a denture.

[0005] The present invention is achieved by first providing a potassium feldspar crystal glaze powder for dentures, comprising the following components: 60-67% SiO2, 11-12.5% ​​Al2O3, 1.4-1.7% B2O3, 0.7-0.85% CaO, 1.25-1.45% ZnO, 2.5-2.9% Li2O, 2.5-2.9% Na2O, 7-8% K2O, 0.4-0.5% ZrO2, 1-1.2% MgO, 0.15-0.25% Y2O3, 1.4-1.6% BaO and 2-8% Sc2O3.

[0006] The present invention also provides a method for preparing potassium feldspar crystal glaze powder for dentures, comprising the following steps:

[0007] 1) Prepare ingredients according to the above formula and mix thoroughly to obtain a mixed material;

[0008] 2) putting the mixed material into a platinum crucible, melting it, and immediately pouring it into water for quenching to obtain a molten block;

[0009] 3) The frit is subjected to disc grinding, sieving, ball milling and spray drying to obtain glaze powder.

[0010] Preferably, in step 2), the melting condition is melting at 1550° C. for 50 min.

[0011] Further preferably, in step 3), the frit is passed through a 60-mesh sieve after disc grinding, and the ball milling conditions are: using a zirconia ball mill and 5 mm diameter zirconia grinding balls, a ball-to-material water ratio of 3:1:1, a rotation speed of 350 r / min, and ball milling for 40 min.

[0012] More preferably, in step 3), the particle size of the obtained glaze powder is 3-5 μm.

[0013] The present invention also provides a denture, comprising a denture restoration and a glaze surface formed on the surface of the denture restoration, wherein the glaze surface is formed using the above-mentioned glaze powder.

[0014] Compared with the prior art, the advantages of the present invention are:

[0015] Adding Sc2O3 to the crystalline glaze can affect the crystallization of the crystal phase in the glaze and improve the process performance of the glaze. After firing, the microhardness, mechanical strength and refractive index of the glaze surface are significantly improved, and the combination with the denture restoration is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 DSC curves of glaze powder with different Sc2O3 contents;

[0017] Figure 2 XRD patterns of glazes with different Sc2O3 contents;

[0018] Figure 3 SEM photos of crystalline glazes with different Sc2O3 contents after sintering (a)~(d);

[0019] Figure 4 The glaze hardness of crystalline glaze with different Sc2O3 contents;

[0020] Figure 5 is the compressive strength of crystalline glazes with different Sc2O3 contents;

[0021] Figure 6 is the refractive index of crystalline glazes with different Sc2O3 contents;

[0022] Figure 7is the visible light transmittance of crystalline glazes with different Sc2O3 contents;

[0023] Figure 8 The thermal expansion curves of crystalline glazes with different Sc2O3 contents;

[0024] Fig. 9 is the thermal expansion curve of tetragonal zirconia ceramics;

[0025] Fig.10 This is the EDS diagram of the cross section of the crystalline glaze and the zirconia body;

[0026] Fig.11 SEM photos of the cross section of the crystalline glaze and zirconia body (a) and EDS-mapping images of each element (b) to (h);

[0027] Fig.12 SEM photographs of the cross-section of the crystalline glaze and zirconia body at different magnifications (a) to (f). DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0029] 1. Reagents and Materials

[0030] The main raw materials of potassium feldspar crystalline glaze are chemically pure SiO2, B2O3, BaCO3, Al2O3, Li2CO3, Na2CO3, K2CO3, CaCO3, MgO, ZnO, Y2O3, and ZrO2. The formula is designed by adding different contents of Sc2O3. The chemical composition of the samples is shown in Table 1.

[0031] Table 1 Frit sample design composition

[0032]

[0033] 2. Glaze block sample preparation

[0034] The ingredients were prepared according to the formula in Table 1, mixed thoroughly and put into a platinum crucible, melted at 1550°C for 50 minutes, and immediately poured into water for quenching to obtain a frit. The frit was disc-milled, passed through a 60-mesh sieve, ball-milled for 40 minutes (using a zirconia ball mill and a 5mm diameter zirconia grinding ball, a ball-to-water ratio of 3:1:1, and a rotation speed of 350r / min), and spray-dried to obtain a glaze powder (particle size 3-5μm).

[0035] Take an appropriate amount of glaze powder and shape it in a specific square (22mm*16mm) mold under a pressure of 2.5t, and then use an isostatic press to isostatically press it under a pressure of 220Mpa to form a glaze block.

[0036] 3. Effect of Sc2O3 on glaze crystallization properties

[0037] Take part of the glaze powder for DSC test. Figure 1 It is known that the exothermic valley caused by glass transition of glaze powder samples G1, G2, G3, and G4 all appeared near 320℃. With the increase of Sc2O3 content, the crystallization became more complete, the glass transition gradually became less obvious, and the exothermic valley became smoother. The endothermic peaks generated by the formation of crystal nuclei all appeared near 574℃, and the exothermic valleys caused by crystallization appeared at 958.5, 924.7, 903.8, and 827.8℃, respectively. It can be seen that with the increase of Sc2O3 content, the crystallization temperature of the crystalline glaze gradually decreased, and the addition of Sc2O3 promoted the crystallization of the crystalline glaze. According to the DSC curve, the sintering process parameters of the sample glaze blocks G1, G2, G3, and G4 were determined to be heated to 959, 925, 904, and 828℃, respectively, at a heating rate of 10℃ / min and kept warm for 30min.

[0038] Figure 2 This is the XRD spectrum of the surface of the glaze block sample after sintering. It can be seen from the figure that a small amount of potassium feldspar crystals are precipitated in sample G1. As the Sc2O3 content increases, samples G2, G3, and G4 precipitate potassium feldspar and generate scandium silicate crystals. According to the XRD spectrum, the crystallinity of the crystalline glaze is calculated by Rieveld full spectrum fitting. The results show that after sintering, the crystallinity of samples G1, G2, G3, and G4 first increases and then decreases to 6.59%, 14.13%, 84.8%, and 76.93%, respectively. Sc2O3 is a network intermediate oxide in silicate glass with a coordination state of 6. Sc2O3 can participate in the silicate network structure, and when added in excess, it precipitates in the form of scandium silicate crystals. The precipitated scandium silicate crystals provide heterogeneous nucleation points for potassium feldspar inside the glaze, reduce the crystallization energy barrier, and thus promote the crystallization of potassium feldspar crystal phase.

[0039] 4. Effect of Sc2O3 on glaze microstructure

[0040] Figure 3 This is the SEM photo of the glaze surface of the sintered glaze block samples G1, G2, G3, and G4 after being etched with 5% HF for 30 seconds. It can be seen from the figure: Figure 3 (a) Sample without Sc2O3 addition, a small amount of regular angular columnar K(Si3Al)O8 crystals were precipitated; Figure 3(b) Sc2O3 3.33% sample, the number of crystals increased, the crystal size increased, and a small amount of fine rod-shaped Sc2Si2O7 crystals attached to the surface of K(Si3Al)O8 crystals; Figure 3 (c) The number of K(Si3Al)O8 crystals precipitated from the Sc2O3 6.67% sample is larger, the grain size continues to increase, and more Sc2Si2O7 crystals are generated, which not only adhere to the surface of K(Si3Al)O8 crystals, but also erode and grow from the inside to the surface; Figure 3 (d) The size of K(Si3Al)O8 crystals precipitated from the Sc2O310.00% sample further increases, and the erosion of Sc2Si2O7 crystals becomes more obvious, spreading on the surface and inside of the K(Si3Al)O8 crystals.

[0041] 5. Effect of Sc2O3 on mechanical properties of crystalline glaze

[0042] The sintered glaze block sample was bonded to the holder and fixed on the grinder. The cylindrical glaze block sample with a diameter of 12 mm was cut by plunge grinding, and then cut into a circular sample with a thickness of 1.6 mm by a diamond inner circle cutting machine. Both sides were flat-ground to 1.2 mm, and finally the sample plane was polished by a metallographic sample polishing machine. The Knoop hardness and compressive strength were tested by a Knoop hardness tester and a universal material testing machine, respectively.

[0043] Figure 4 and Figure 5 The results of the Knoop hardness and compressive strength test of the crystalline glaze samples are shown in Figure 2. The results show that as the Sc2O3 content increases from 0% to 6.67%, the Knoop hardness and compressive strength of the crystalline glaze increase significantly, reaching the maximum values ​​of 508.86HK and 132.33MPa respectively when the Sc2O3 content is 6.67%. However, as the Sc2O3 content continues to increase beyond 6.67%, the Knoop hardness and compressive strength of the crystalline glaze decrease.

[0044] Generally speaking, the crystal type and micromorphology in the crystalline glaze have a great influence on its mechanical properties. Combining the XRD test results with the SEM scanning photo analysis, the sample with a Sc2O3 content of 0.00% has less crystal phase, most of which is glass phase, and the hardness strength is low. When the Sc2O3 content is 3.33%, the crystallinity increases, and more K(Si3Al)O8 crystals with higher hardness (Knoop hardness 691.15) are precipitated, resulting in an increase in hardness.

[0045] When the Sc2O3 content is 6.67%, the crystallinity reaches its maximum value, the K(Si3Al)O8 crystals are staggered and closely arranged, the grain size is moderate, and the precipitated Sc2Si2O7 crystals fill the gaps between the K(Si3Al)O8 grains, which increases the density and hardness. At the same time, when the glaze surface encounters pressure, this microstructure can hinder the expansion of cracks to the greatest extent, thereby improving the compressive strength. When the Sc2O3 content is increased to 10.00%, excessive addition of Sc2O3 leads to an increase in grain size and an increase in gaps, resulting in a decrease in density, and a decrease in hardness and strength.

[0046] 6. Effect of Sc2O3 on the optical properties of crystalline glaze

[0047] The sintered glaze block was cut into 16mm×18mm slices and ground to 1.0mm thick. After polishing on both sides, it was used for refractive index and visible light transmittance testing. Figure 6 and Figure 7 The refractive index and visible light transmittance test results of the crystalline glaze samples are shown in the figure. As the Sc2O3 content increases from 0% to 6.67%, the refractive index of the crystalline glaze gradually increases, reaching a maximum value of 1.531 when the Sc2O3 content is 6.67%. However, as the Sc2O3 content continues to increase and exceeds 6.67%, the refractive index of the crystalline glaze decreases. The visible light transmittance decreases first and then increases with the increase of Sc2O3 content, and is 44.53%, 43.99%, 43.05%, and 43.65% respectively.

[0048] The refractive index of a material usually refers to the ratio of the speed of light in a vacuum to the speed of light in the material. The refractive index of a crystalline glaze is related to the refractive index, crystallinity and density of the glass phase. The refractive index of the glass phase mainly depends on the polarizability of the ions inside the glass and the density of the glass. 3+ With stable +3 valence, large ionic radius and high polarizability, the addition of Sc2O3 will increase the refractive index of the glass phase. With the gradual precipitation of potassium feldspar crystals (refractive index 1.518-1.533) and the combined effect of the refractive index of the glass phase, the refractive index of the crystalline glaze increases when the amount of Sc2O3 added increases from 0.00% to 6.67%. When the amount of Sc2O3 added reaches 10.00%, the density of the crystalline glaze decreases due to the increase in grain size and gaps. At this time, the density plays a major role in the influence of the refractive index. The decrease in density causes the propagation speed of light waves in the glass to increase and the refractive index to decrease.

[0049] According to the Ryaleigh-Gans model, the permeability can be expressed by the turbidity σ, as shown in formula (1).

[0050]

[0051] Where: σ is turbidity, m -1 ; N is the particle density, μm -3 ; V is the particle volume, nm 3 ; n is the refractive index; k = 2π / λ, λ is the wavelength, nm; R is the particle radius, nm; Δn is the refractive index difference between the residual glass phase and the crystal phase. When the Sc2O3 content is 0%, the sample has the highest visible light transmittance. This is because the sample has a low crystallinity at this time, which makes the density of the grains low, and the content of the glass phase is high, the turbidity is low, which makes the visible light transmittance relatively high. From formula (1), it can be seen that when the Sc2O3 content increases from 0.00% to 6.67%, potassium feldspar crystals continue to precipitate, the increase in crystallinity increases the grain density, and at the same time, the increase in grain radius, grain volume, and the refractive index of the glaze eventually increases the turbidity and reduces the transmittance. When the Sc2O3 content increases to 10.00%, the decrease in crystallinity leads to a decrease in grain density. At the same time, the decrease in the refractive index of the glaze eventually leads to a decrease in turbidity. In addition, due to the increase in grain size, the increase in gaps is conducive to the passage of light, and the transmittance increases.

[0052] 7. Effect of Sc2O3 on thermal expansion coefficient of crystalline glaze

[0053] The sintered glaze block samples and tetragonal zirconia blanks (Aierchuang Biomaterials Co., Ltd., China) were cut into cylindrical glaze block samples with a length of 1.5 mm and a diameter of 6 mm. After grinding both ends, the thermal expansion coefficient of the samples was tested using a thermal expansion coefficient tester. Figure 8 and Fig. 9 The thermal expansion curves of the sintered glaze block and the tetragonal zirconia body are shown in Figure 1. The thermal expansion coefficient is calculated in the temperature range of 225 to 500 °C. As can be seen from the figure, the thermal expansion coefficients of the crystalline glaze are 8.52×10 -6 8.30×10 -6 ,7.36×10 -6 ,7.23×10 -6 / ℃(225~500℃), the thermal expansion coefficient of the green tetragonal zirconia ceramic is 8.25×10 -6 / ℃(225~500℃).

[0054] Glaze is a substance attached to the surface of the body. Only when the thermal expansion coefficients of the body and glaze are equal or very close, there is no stress or very little stress in the glaze. According to theoretical calculations and practical data, when α 釉 <α 坯 The difference between the expansion coefficients of the body and glaze should not exceed (1-4)×10 -6 / ℃: When α 釉 >α 坯 When the difference between the two should be less than 0.4×10 -6 / ℃. If the thermal expansion coefficients of the two do not match, the glaze layer will experience stress due to rapid temperature changes during glaze firing or use. If this stress exceeds the glaze strength, it will cause cracking or falling off. When the Sc2O3 content is 0.00% and 3.33%, the thermal expansion coefficient of the crystalline glaze is greater than that of the body. The difference in thermal expansion coefficients of the body and glaze is 0.27×10 -6 / ℃ reduced to 0.05×10 -6 / ℃, all less than 0.4×10 -6 / ℃: When the Sc2O3 content is 6.67% and 10.00%, the thermal expansion coefficient of the crystalline glaze is smaller than that of the body, and the difference in thermal expansion coefficients of the body and glaze is 0.89×10 -6 / ℃ increased to 1.02×10 -6 / ℃, all less than (1~4)×10 -6 / ℃: This shows that the difference in thermal expansion coefficient between the crystalline glaze and the body is within the range and meets the practical standards.

[0055] The thermal expansion coefficient of crystalline glaze is determined by the compactness of the crystal structure and the ratio of the crystal phase to the residual glass phase. By consulting the literature, it can be found that the thermal expansion coefficient of potassium feldspar crystals precipitated in the crystalline glaze system is 5.22×10 -6 / ℃(20~650℃)

[17] As the Sc2O3 content increases from 0% to 6.67%, the crystallinity of potassium feldspar gradually increases, causing the thermal expansion coefficient to gradually decrease. When the Sc2O3 content reaches 10%, the crystallinity of potassium feldspar decreases, but the growth of grains leads to an increase in gaps and a decrease in the density of crystal arrangement, which ultimately causes the thermal expansion coefficient to still decrease.

[0056] 8. Analysis of body-glaze bonding

[0057] A glaze powder with a thermal expansion coefficient closest to that of the tetragonal zirconia green body and a Sc2O3 content of 3.33% was selected and mixed with deionized water in a mass ratio of 2:1 and applied to a tetragonal zirconia ceramic green body. After sintering, EDS and SEM tests were performed on the cross section. Fig.10 Table 2 shows the mass ratio and atomic percentage of each element in the cross section of the crystalline glaze and zirconia body. Fig.11 and Fig.12 They are EDS-mapping images (a) to (h) of the elements contained in the crystals of the crystalline glaze cross section and SEM photos at different magnifications (a) to (f).

[0058] Depend on Fig.10 As can be seen from Table 2, the proportion of each element in the crystalline glaze is consistent with the crystalline glaze formula.

[0059] Depend on Fig.11It can be seen that after sintering, the components in the glaze penetrate into the surface layer of the body, and the components in the body also diffuse or melt into the glaze. Through the effects of diffusion and melting, the chemical composition and physical properties of the contact surface are between the body and the glaze layer, forming an intermediate layer. It plays a certain role in adjusting the difference between the body and the glaze, easing the stress in the glaze layer, and improving the bonding performance of the body and the glaze.

[0060] Depend on Fig.12 It can be seen that a large number of potassium feldspar crystals of moderate size are generated in the area close to the surface of the tetragonal zirconia body. These crystals adhere to the surface of the tetragonal zirconia and penetrate into the glaze layer, which can act as wedges and strengthen the bonding between the body and the glaze.

[0061] Table 2 Mass ratio and atomic proportion of each element in the cross section of crystalline glaze and zirconia body

[0062]

Claims

1. A potassium feldspar crystal glaze powder for dentures, characterized in that: Calculated by mass percentage, it includes the following components: 60-67% SiO2, 11-12.5% ​​Al2O3, 1.4-1.7% B2O3, 0.7-0.85% CaO, 1.25-1.45% ZnO, 2.5-2.9% Li2O, 2.5-2.9% Na2O, 7-8% K2O, 0.4-0.5% ZrO2, 1-1.2% MgO, 0.15-0.25% Y2O3, 1.4-1.6% BaO and 2-8% Sc2O3.

2. A method for preparing potassium feldspar crystal glaze powder for dentures, characterized in that: The steps include: 1) preparing ingredients of the potassium feldspar crystal glaze powder for artificial teeth according to claim 1, and mixing them thoroughly to obtain a mixed material; 2) Put the mixed material into a platinum crucible, melt it, take it out and immediately pour it into water for quenching to obtain a molten block; 3) The molten block is subjected to disc grinding, sieving, ball milling and spray drying to obtain glaze powder.

3. The method for preparing potassium feldspar crystal glaze powder for denture according to claim 2, characterized in that: In step 2), the melting condition is melting at 1550° C. for 50 min.

4. The method for preparing potassium feldspar crystal glaze powder for denture according to claim 2, characterized in that: In step 3), the frit is disc-milled and then passed through a 60-mesh sieve. The ball milling conditions are as follows: a zirconia ball milling jar and 5-mm-diameter zirconia grinding balls are used, the ball-to-material water ratio is 3:1:1, the rotation speed is 350 r / min, and the ball milling is performed for 40 min.

5. The method for preparing potassium feldspar crystal glaze powder for denture according to claim 2, characterized in that: In step 3), the particle size of the obtained glaze powder is 3-5 μm.

6. A denture, characterized in that: The invention comprises a denture restoration and a glaze formed on the surface of the denture restoration, wherein the glaze is formed by using the glaze powder according to claim 1.